(How) do universities listen? Evidence from institutional websites of the world's top universities - Sueldo, Mariana (European Public & Social Innovation Review, 2024)
Introduction: this study investigates the implementation of organizational listening methods in Higher Education through a comparative analysis of institutional websites from top global universities and leading Lithuanian institutions. Emphasizing the role of these websites as pivotal digital platforms, the research aims to discern the extent to which universities facilitate two-way communication with stakeholders through digital platforms. Methodology: Websites were selected based on world university rankings, encompassing institutions from each continent. Websites were selected based on global university rankings, spanning institutions across continents. Qualitative content analysis employed predefined and emergent categories to evaluate interactivity and organizational listening features on these platforms. Findings reveal consistent stakeholder mapping but significant disparities in communication tools and channels, which impacts real-time, asynchronous, and symmetric engagement effectiveness. Communication structures range from integrated governance roles to fragmented responsibilities, influencing stakeholder accessibility and institutional transparency. Discussion: implications for organizational communication practices are discussed, highlighting strategies to enhance stakeholder engagement via institutional websites. The study underscores the pivotal role of communication management teams in fostering transparency and responsiveness. Conclusions: advocating for leveraging technological advancements, conclusions propose transforming websites into proactive platforms for organizational listening. Recommendations emphasize developing tailored communication strategies to optimize engagement and effectiveness in Higher Education contexts.